Infantile hepatic hemangioendothelioma in a newborn - Silva,Joana (2021)
Abstract Infantile hepatic hemangioendothelioma is the most common benign hepatic vascular tumor in infants younger than six months and may undergo spontaneous regression during the first years of life. Diagnosis of these lesions in preterm newborns can be challenging, with its timing and accuracy relevant to avoid inappropriate therapeutic measures.